Economic Significance of Creeping Anchors Tribulus Terrestris L (Texas Journal of Agriculture and Biological Sciences, 2023)
The article gives the economic significance of creeping anchors-Tribulus terrestris L. A complete botanical description, scientific classification, synonyms of the plant, distribution and habitat, brief chemical composition, pharmacological properties, economic significance: food and medicinal, procurement of raw materials, use in medicine, contraindications and side effects are given